Development of a Clinical Framework for Mirror Therapy in Patients with Phantom Limb Pain: An Evidence‐based Practice Approach. Issue 4 (16th April 2015) - Rothgangel, Andreas; Braun, Susy; de Witte, Luc; Beurskens, Anna; Smeets, Rob
Abstract: Objective: To describe the development and content of a clinical framework for mirror therapy (MT) in patients with phantom limb pain (PLP) following amputation. Methods: Based on an a priori formulated theoretical model, 3 sources of data collection were used to develop the clinical framework. First, a review of the literature took place on important clinical aspects and the evidence on the effectiveness of MT in patients with phantom limb pain. In addition, questionnaires and semi‐structured interviews were used to analyze clinical experiences and preferences of physical and occupational therapists and patients suffering from PLP regarding the application of MT. All data were finally clustered into main and subcategories and were used to complement and refine the theoretical model. Results: For every main category of the a priori formulated theoretical model, several subcategories emerged from the literature search, patient, and therapist interviews. Based on these categories, we developed a clinical flowchart that incorporates the main and subcategories in a logical way according to the phases in methodical intervention defined by the Royal Dutch Society for Physical Therapy. In addition, we developed a comprehensive booklet that illustrates the individual steps of the clinical flowchart. Conclusions: In this study, a structured clinical framework for the application of MT in patients with PLP was developed. This framework is currently being tested for its effectiveness in a multicenter randomized controlled trial.